Keeping track of and recognizing the value of Public Involvement work in dementia research - Georges, Jean; Diaz-Ponce, Ana; Lamirel, Daphne; Moradi-Bachiller, Soraya; Gove, Dianne (Frontiers in Neurology, 2022)
The Public Involvement (PI) of people with dementia is slowly but progressively moving from a “nice to have” to a “must have” element of good quality dementia research. Research funders and ethics committees increasingly ask for evidence of the planning of such involvement. The actual conduct and outcome of PI are, however, unfortunately typically under or inadequately reported. In this article, we provide an overview of what PI is, why it is important to dementia research and Alzheimer Europe’s approach to PI. We draw on our recent experience of compiling a set of examples of PI in different European projects in publicly available sources. This highlighted the difficulty of finding information about PI activities and the almost total lack of details of such activities in formal reports, official records and/or public project websites. In this article, we emphasise gaps and call for more stringent conditions for the inclusion and reporting of PI work with regard to the approval and funding of dementia research projects. We call for the establishment of obligatory reporting on the nature, specific challenges and impact of PI in dementia research in formal reports (e.g. to funders), on public project websites and in peer-reviewed articles. Such reporting should cover several key factors such as who was involved, how they were involved and what impact PI had on the research process.